1990
DOI: 10.1103/physrevlett.65.251
|View full text |Cite
|
Sign up to set email alerts
|

Chern-Simons Terms andnField in Haldane's Model for the Quantum Hall Effect without Landau Levels

Abstract: It is shown that the nonzero quantized value of the Hall conductivity in Haldane's model [Phys. Rev. Lett. 61, 20151 appears because the electron Green's function is a topologically nontrivial function of momentum and frequency. If the n field is introduced in this model then the same topological invariant, defined in the momentum-frequency space, gives a nonzero coefficient for the Hopf-ChernSimons term of the n field. A Chern-Simons-like term, which mixes the electromagnetic and n fields and determines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 14 publications
1
67
0
Order By: Relevance
“…The anomalous Hall effect was studied for this model earlier in Ref. [79], and the anomalous Nernst effect was discussed in Ref. [80].…”
Section: Appendix B: Chiral Superconductors Vs the Trsb Topological mentioning
confidence: 99%
See 1 more Smart Citation
“…The anomalous Hall effect was studied for this model earlier in Ref. [79], and the anomalous Nernst effect was discussed in Ref. [80].…”
Section: Appendix B: Chiral Superconductors Vs the Trsb Topological mentioning
confidence: 99%
“…For non-superconducting systems, the current operator can be expressed in terms of the derivatives ∂Ĥ/∂p of the HamiltonianĤ with respect to the electron quasimomenta p. For a topologically non-trivial band structure, the off-diagonal matrix elements of the current operator between different bands produce a non-zero Berry curvature, and the anomalous Hall conductivity can be expressed completely in terms of the Berry curvature [46,47,[77][78][79][80].…”
Section: Appendix B: Chiral Superconductors Vs the Trsb Topological mentioning
confidence: 99%
“…The Hall conductivity ͑in units of e 2 / h͒ associated to a fully gapped model is generically given by 20,21 …”
Section: A Quantized Hall Conductivity Of Individual Valleysmentioning
confidence: 99%
“…The Hamiltonian (4) with t ′ = 0 and µ = 0 was studied in Ref. [13], where it was found that this system exhibits the intrinsic quantum Hall effect without an external magnetic field. This confirms that the time-reversal symmetry is spontaneously broken in the (d + id) density-wave state.…”
mentioning
confidence: 99%